Transcriptome Dynamics in the Developing Larynx, Trachea, and Esophagus - Wendt, Kristy D.; Brown, Jared; Lungova, Vlasta; Mohad, Vidisha; Kendziorski, Christina; Thibeault, Susan L. (Frontiers in Cell and Developmental Biology, 2022)
The larynx, trachea, and esophagus share origin and proximity during embryonic development, with clinical and experimental evidence supporting the existence of neurophysiological, structural, and functional interdependencies before birth. This investigation provides the first comprehensive transcriptional profiling of all three organs during embryonic organogenesis, where differential gene expression gradually assembles the identity and complexity of these proximal organs from a shared origin in the anterior foregut. Through the application of bulk RNA sequencing and gene network analysis of differentially expressed genes (DEGs), both within and across developing embryonic mouse larynx, esophagus, and trachea, we identified co-expressed modules of genes enriched for key biological processes. Organ-specific temporal patterns of gene activity corresponding to gene modules within and across shared tissues during embryonic development (E10.5-E18.5) are described, and the laryngeal transcriptome during vocal fold development and maturation from birth to adult is characterized in the context of laryngeal organogenesis. The findings of this study provide new insights into interrelated gene sets governing organogenesis of this tripartite organ system within the aerodigestive tract, with relevance to multiple families of disorders defined by cardiocraniofacial syndromes.